Determination of platinum in mineral raw materials by switching chronoamperometry; IOP Conference Series: Earth and Environmental Science; Vol. 21: XVIII International Scientific Symposium in Honour of Academician M. A. Usov: Problems of Geology and Subsurface Development 7–11 April 2014, Tomsk, Russia - Pakrieva E. G. Ekaterina Germanovna (High Technologies in Raw Hydrocarbon and Mineral Conversion, 2014)
Title screen